Assessing urban lifeline systems immediately after seismic disaster based on emergency resilience. Issue 12 (1st December 2016) - Zhao, Xudong; Cai, Hao; Chen, Zhilong; Gong, Huadong; Feng, Qilin
Abstract: Resilience is an emerging concept for analyzing the dynamic performance of critical infrastructures during the post-disaster recovery process. Although a number of studies examined how to assess long-term resilience (1 year +), very few have investigated short-term resilience (few days to several weeks following a disaster). This study presents the new concept of 'emergency resilience' and the framework for assessing this short-term resilience for urban lifeline systems in the emergency recovery stage. This framework can quantify differences in system performance (pre-disaster vs. post-recovery) using the new 'recovery degree' feature. It also integrates a new performance response function which is based on network equilibrium theory to assess emergency resilience in both the technical and organisational dimensions. In the case study of the water pipeline network in Lianyungang, China, the results showed that the levels of the recovery budget b and recovery resource r had different effects on emergency resilience R in seismic disaster. Furthermore, it is demonstrated how the concept and its assessment framework can provide a quick reference tool for optimal decision-making under various scenarios. This study also examined the effects of two anti-seismic reconstruction measures, namely meshed expansion and ductile retrofitting, on the expected emergency resilience of the water pipeline network.